-12-6=-2(d+3)-10d

Simple and best practice solution for -12-6=-2(d+3)-10d equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12-6=-2(d+3)-10d equation:


Simplifying
-12 + -6 = -2(d + 3) + -10d

Combine like terms: -12 + -6 = -18
-18 = -2(d + 3) + -10d

Reorder the terms:
-18 = -2(3 + d) + -10d
-18 = (3 * -2 + d * -2) + -10d
-18 = (-6 + -2d) + -10d

Combine like terms: -2d + -10d = -12d
-18 = -6 + -12d

Solving
-18 = -6 + -12d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '12d' to each side of the equation.
-18 + 12d = -6 + -12d + 12d

Combine like terms: -12d + 12d = 0
-18 + 12d = -6 + 0
-18 + 12d = -6

Add '18' to each side of the equation.
-18 + 18 + 12d = -6 + 18

Combine like terms: -18 + 18 = 0
0 + 12d = -6 + 18
12d = -6 + 18

Combine like terms: -6 + 18 = 12
12d = 12

Divide each side by '12'.
d = 1

Simplifying
d = 1

See similar equations:

| 64p^8q+24p^6q^3+40p^4q^2=0 | | -47n+-34=-34 | | -3(3m-1)=-6(m-6) | | 8p^3+3p^2q^2+5q=0 | | 4/txt-1/6xt=1/txt | | 5x+35=5x+20 | | 7(x+1)+6(x+1)=7x-7 | | -47+-34=-34 | | 8x^2+56x+16=0 | | -47+-47=-34 | | 9a^2-8b^2=0 | | 7(12+7n)=7(6n-8) | | 4u^2-33u+35=0 | | C=100+55x | | 700-35x=450+13x | | 2xa+3a=10x+15 | | 4m=-10+2m | | 5m^3-8m^2+3m=0 | | p+[-3]=14 | | 4x^2-16xy-7x+28y=0 | | 87/3/4=x/5 | | 87÷3/4=x/5 | | 28a=-196 | | (1/e^x)=0 | | 5/9m-5=10 | | 1.5=q+0.6 | | f(x)=220+8x^3+x^4 | | 9x+14=56-x | | 2x-2=-x+13 | | 5-3p=-11+5p | | 4(2m-3)+4m+7=67 | | x+9=17+5x |

Equations solver categories